2021
DOI: 10.3389/fendo.2021.707283
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Children With Short Stature: Accurate Determination of Serum Vitamin D Components Using High-Performance Liquid Chromatography–Tandem Mass Spectrometry

Abstract: ObjectiveVitamin D is critical for calcium and bone metabolism. Vitamin D insufficiency impairs skeletal mineralization and bone growth rate during childhood, thus affecting height and health. Vitamin D status in children with short stature is sparsely reported. The purpose of the current study was to investigate various vitamin D components by high-performance liquid chromatography–tandem mass spectrometry (LC-MS/MS) to better explore vitamin D storage of short-stature children in vivo.MethodsSerum circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…One of those researches found that consuming calcium below a specific cutoff value could affect final body height, while increasing calcium intake above the cutoff value didn't increase final body height but increased the body height's growth rate. Some researchers also found that calcium intake didn't correlate with body height (Maharsari, 2018;Winzenberg et al, 2007;Xu et al, 2021). This could happen because calcium has 40-60% absorption rate depending on some factors, like the concentration of calcium ions in the gastrointestinal (GIT) lumen, absorption time of the food in the GIT, and substances that could inhibit calcium absorption, such as phytate and oxalate (Shkembi & Huppertz, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One of those researches found that consuming calcium below a specific cutoff value could affect final body height, while increasing calcium intake above the cutoff value didn't increase final body height but increased the body height's growth rate. Some researchers also found that calcium intake didn't correlate with body height (Maharsari, 2018;Winzenberg et al, 2007;Xu et al, 2021). This could happen because calcium has 40-60% absorption rate depending on some factors, like the concentration of calcium ions in the gastrointestinal (GIT) lumen, absorption time of the food in the GIT, and substances that could inhibit calcium absorption, such as phytate and oxalate (Shkembi & Huppertz, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…From then on, increasing studies have focused on the relationship between C3-epi-25(OH)D and disease or health [24,32,33]. However, most of these have been 5 Oxidative Medicine and Cellular Longevity limited to the VitD storage overestimation, ignoring the role of C3-epi-25(OH)D in disease progression [34,35], and thus failing to provide a more reasonable explanation for the abnormal increase of C3-epi-25(OH)D in pathological conditions. Therefore, this study focused on the difference in C3-epi-25(OH)D levels in RA patients with different severities of CKD and aimed to understand the potential connections between the two.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin K and vitamin D levels in serum were assessed by high-performance liquid chromatography (HPLC) (34)(35)(36). Briefly, 2 ml of venous blood was collected in a standard biochemical tube (red cap tube) and stored at room temperature while being protected from light.…”
Section: Serum Vitamin K /K and (Oh)d Concentrationsmentioning
confidence: 99%